Host‐Guest Systems on the Surface of Functionalized Superparamagnetic Iron Oxide Nanoparticles (SPIONs) Utilizing Hamilton Receptors and Cyanurate Derivative Molecules. Issue 66 (27th October 2021) - Ali, Muhammad; Kataev, Evgeny; Müller, Johannes; Park, Hyoungwon; Halik, Marcus; Hirsch, Andreas
Abstract: The study of hydrogen bonding interactions at the level of functionalized nanoparticles remains highly challenging and poorly explored area. In this work, superparamagnetic iron oxide nanoparticles (SPIONs) were orthogonally functionalized using receptors bearing multiple hydrogen bonding motifs. Pristine SPIONs were modified by wet chemical processes with Hamilton receptors (hosts), or cyanurate‐guest molecules linked to phosphonic acid moieties for monolayer functionalization. The modified surfaces were fully characterized and the number of attached ligands on the surface were determined. The host‐guest interactions on the interface of modified SPIONs were investigated by using UV‐Vis spectroscopic titrations. Functionalized SPIONs demonstrated two to three magnitudes stronger binding affinities as compared to the related molecular interactions in solution due to synergistic effects on complex surface environment. Higher supramolecular binding ratios of host‐guest interactions on the modified surface were emerged. These studies provide fundamental insights into supramolecular complexations on the surface at solid‐liquid interface systems with applications in engineered nanomaterials, nano‐sensing devices, and drug delivery systems. Abstract : Fundamental insight of supramolecular interactions on the surface of modified superparamagnetic iron oxide nanoparticles (SPIONs) utilizing host‐guest chemistry among Hamilton receptors and cyanurate derivatives. Binding constants of host‐guest systems on the surface of nanoparticles showed stronger binding constant and higher binding ratio compared to free molecules in the solutions, due to synergistic effect on complex surface environment.